Divergent Population Genetic Structure of the Endangered Helianthemum (Cistaceae) and Its Implication to Conservation in Northwestern China - Su, Zhihao; Richardson, Bryce A.; Zhuo, Li; Jiang, Xiaolong (Frontiers in Plant Science, 2017)
Population genetic studies provide a foundation for conservation planning, especially for endangered species. Three chloroplast SSRs (mtrnSf-trnGr, mtrnL2-trnF, and mtrnL5-trnL3) and the internal transcribed spacer were used to examine the population structure of Helianthemum in northwestern China. A total of 15 populations of the genus were collected. Nine chloroplast haplotypes and two nuclear genotypes were detected. Both the nuclear and chloroplast data showed two lineages in Helianthemum songaricum, respectively distributed in Yili Valley and western Ordos Plateau. A total of 66.81 % (p < 0.001) of the genetic variation was supported by this lineage split. A Mantel test showed a significant correlation between genetic distance and geographical distance (r = 0.937, p < 0.001). Based on genetic analyses, cpSSRs data support strong genetic divergence between regions. We speculate that the climate change during the late Tertiary and early Quaternary isolated H. songaricum into their current distribution, resulting in interruption of gene ﬂow, leading to isolation and genetic divergence between the two regions. Meanwhile, possible selfing would increase genetic drift in small fragmented populations, that might account for the observed genetic divergence in both regions. Given the loss of genetic diversity and genetic divergence in small populations of Helianthemum in northwestern China immediate conservation management steps should be taken on the species.